Carbon-based nanomaterials for removal of chemical and biological contaminants from water: A review of mechanisms and applications. (September 2015) - Smith, Sean C.; Rodrigues, Debora F.
Abstract: In recent years, significant discoveries related to antimicrobial and adsorption properties of carbon-based nanomaterials have led to new avenues for removal of various biological and organic/inorganic contaminants in drinking water. Furthermore, progress in the synthesis of multifunctional nanocomposites paves the way for their application in advanced water treatment system design. This review article describes and compares the adsorptive and antimicrobial properties of four common classes of carbon nanomaterials: single- and multi-walled carbon nanotubes, graphene, and graphene oxide, as well as some of their most important polymeric and metallic nanocomposites. Barriers for application of these nanomaterials in sustainable water treatment are also addressed.